Enzymatic Late‐Stage Modifications: Better Late Than Never. Issue 31 (8th March 2021) - Romero, Elvira; Jones, Bethan S.; Hogg, Bethany N.; Rué Casamajo, Arnau; Hayes, Martin A.; Flitsch, Sabine L.; Turner, Nicholas J.; Schnepel, Christian
Abstract: Enzyme catalysis is gaining increasing importance in synthetic chemistry. Nowadays, the growing number of biocatalysts accessible by means of bioinformatics and enzyme engineering opens up an immense variety of selective reactions. Biocatalysis especially provides excellent opportunities for late‐stage modification often superior to conventional de novo synthesis. Enzymes have proven to be useful for direct introduction of functional groups into complex scaffolds, as well as for rapid diversification of compound libraries. Particularly important and highly topical are enzyme‐catalysed oxyfunctionalisations, halogenations, methylations, reductions, and amide bond formations due to the high prevalence of these motifs in pharmaceuticals. This Review gives an overview of the strengths and limitations of enzymatic late‐stage modifications using native and engineered enzymes in synthesis while focusing on important examples in drug development. Abstract : Late‐stage modification is an indispensable approach for compound diversification in synthesis. Since enzymes offer particularly powerful means for mild, catalyst‐controlled functionalisations, in recent years several novel biocatalytic methods have emerged enabling a broad array of orthogonal reactions. Herein, the wide range of late‐stage biotransformations is reviewed and various enzyme classes along with topical examples are discussed.